Palynology of Medicinal Plant Families: Pollen Diversity and Its Pharmacobotanical Significance (International Journal of Scientific Research in Science and Technology, 2025)
This comprehensive review explores the significance of palynology, focusing on the study of plant pollen, spores, and microscopic organisms, and its relevance to the reproductive and medicinal aspects of flowering plants. Emphasizing pollen morphology as a key factor in plant reproduction, the review delves into parameters such as size, shape, symmetry, and aperture. The detailed examination of pollen grains covers their morphological characteristics, with specific studies on plant families such as Liliaceae, Rubiaceae, Verbenaceae, and Apocynaceae using light and scanning electron microscopy. Taxonomic implications and diverse features observed in different plant genera are highlighted. The medicinal importance of plants, especially in preventing and treating diseases, is emphasized, with examples of widely used medicinal herbs. In summary, this review provides valuable insights into palynology, pollen morphology, and the medicinal significance of plants, offering a comprehensive understanding of these botanical wonders.
Keywords: Pollen morphology; Medicinal importance; SEM; TEM; LM